Optical mouse acting as biospeckle sensor - Melo da Silva, Michel (2010)
In this work we propose some experiments with the use of optical computer mouse, associated to low cost lasers that can be used to perform several measurements with applications in industry and in human health monitoring. The mouse was used to grab the movements produced by speckle pattern changes and to get information through the adaptation of its structure. We measured displacements in wood samples under strain, variations of the diameter of an artery due to heart beat and, through a hardware simulation, the movement of an eye, an experiment that could be of low cost help for communication to severely handicapped motor patients. Those measurements were done in spite of the fact that the CCD sensor of the mice is monolithically included into an integrated circuit so that the raw image cannot be accessed. If, as was the case with primitive optical mouse, that signal could be accessed, the quality and usefulness of the measurements could be significantly increased. As it was not possible, a webcam sensor was used for measuring the drying of paint, a standard phenomenon for testing biospeckle techniques, in order to prove the usefulness of the mouse design. The results showed that the use of the mouse associated to a laser pointer could be the way to get metrological information from many phenomena involving the whole field spatial displacement, as well as the use of the mouse as in its prime version allowed to get images of the speckle patterns and to analyze them.